ADAPTIVE MANAGEMENT OF ISLAMIC BOARDING SCHOOLS IN THE GLOBAL ERA: A Case Study of Assunniyyah Islamic Boarding School, Jember: MANAJEMEN ADAPTIF PESANTREN DI ERA GLOBAL: Studi pada Pesantren Assunniyyah Jember - Zaman, Ahmad; Abd. Muis Tabrani; Amak Fadholi; Harapandi Dahri (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2026)
In responding to globalization and modernization, Islamic boarding schools must adapt without losing their traditional identity. This study aims to analyze the institutional management adaptation strategy of Pesantren Assunniyyah in addressing these dynamics. Using a qualitative approach with a phenomenological design, the research explores the meanings behind the experiences and actions of institutional actors through participant observation, in-depth interviews, and document analysis. The findings indicate that adaptation is carried out through the integration of diniyah and formal education up to the higher education level, the professionalization of services, the development of economic and healthcare units, and the implementation of dual governance based on both traditional values and formal regulations. The theoretical contribution lies in advancing organizational hybridization theory within religious institutions, demonstrating that managerial modernization does not necessarily lead to secularization. This study offers a transformative pesantren management model that balances modern accountability with traditional spiritual values, reinforcing competitiveness and economic independence while preserving core institutional identity.